1973
DOI: 10.1080/03015521.1973.10427646
|View full text |Cite
|
Sign up to set email alerts
|

Animal treading a review of the work of the late D. B. Edmond

Abstract: The late D. B. Edmond was a pioneer in New Zealand of systematic investigations into the influences of treading on pasture. His published work and data in preparation at the time of his dealh are reviewed by colleagues in Grasslands Division, DSIR, and the direction of further work in this field is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
2

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 12 publications
1
39
2
Order By: Relevance
“…Poor pasture performance resulting from treading damage can be caused by restricting rooting of pasture plants (Brown & Evans 1973) and changes in botanical composition (Lambert et al 1985). However, under the conditions of this experiment, where damage only occurred during one main event, reduced pasture growth rates would simply reflect a lower pasture cover and density (Edmond 1974).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Poor pasture performance resulting from treading damage can be caused by restricting rooting of pasture plants (Brown & Evans 1973) and changes in botanical composition (Lambert et al 1985). However, under the conditions of this experiment, where damage only occurred during one main event, reduced pasture growth rates would simply reflect a lower pasture cover and density (Edmond 1974).…”
Section: Discussionmentioning
confidence: 92%
“…However, the potential for soil surface and pasture damage is high as a consequence of animal treading during winter and early spring (Sheath & Boom 1998). Not only is there a cost in terms of reduced plant growth (Brown & Evans 1973;Edmond 1974), but losses of soil particles and nutrients also occur (Cooke 1988). Whole catchment studies have shown that greater soil particle and nutrient losses occur with mob grazing systems (McColl & Gibson 1979) and with cattle-dominant grazing (Lambert et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Damage to soil physical properties can result in more frequent and persistent ponding or soil wetness, inadequate soil aeration, nutrient loss, reduced nutrient uptake efficiency, reduced root penetration, and reduced nutrient accessibility by the plant. Such changes can make soil increasingly difficult to manage (Mulqueen 1988;Mulholland & Fullen 1991), adversely affecting the root environment and decreasing pasture yield (Gradwell 1965;Brown & Evans 1973;Johnson et al 1993;Ledgard et al 1996). Possible off-site effects include increased runoffof water and pollutants (Nguyen et al 1998) to lakes and streams and increased emission of greenhouse gases (CO 2 , CH 4 , N 2 O) (Oenema et al 1997) (Fig.…”
mentioning
confidence: 99%
“…The sharp decline in tiller density in trodden plots was mainly due to physical damage done to the plants by hoof pressure. Brown and Evans (1973) believed that the effect of treading was due to the direct damage to plant growing points, uprooting and breaking of the tillers by hoof action and loss of photosynthetic surfaces. The increased pasture growth rate of damaged sites during the recovery period after treading in both slope classes was associated with an increased tiller number.…”
Section: Discussionmentioning
confidence: 99%
“…Animal types and sizes, stocking intensity, soil types and soil water contents, as well as the duration of treading, may affect the damage to plants and soils. Earlier studies have indicated that a decrease in pasture yield is associated with change in soil physical conditions caused by treading (Brown and Evans, 1973;Johnson et al, 1993;Sheath and Carlson, 1998). Trampling is a significant factor reducing pasture utilization and animal production on dairy farms (Blackwell, 1993) and the recovery rate of pasture during spring (Sheath and Carlson, 1998).…”
Section: Introductionmentioning
confidence: 99%